Adaptivity, adaptability, adapting response, and adaptation result: testing with structural equation modelling on pre-service teachers - Kara, Ahmet; Orum-Cattik, Esra; Eryilmaz, Ali (SPRINGER, 2022)
The aim of this research is to propose a structural equation model that empirically deals with the applicability of the career construction model in explaining the academic and life satisfaction of special education teacher candidates and tests this model. This research studying at a public university located in Turkey, 165 (71.1%) were female and 67 (29.9%) of 232 volunteers participated in a pre-service special education teachers. Two-Dimensional Self-Esteem Scale, Career Adaptability Scale, Career Decision Self-Efficacy Scale, Academic Satisfaction Scale and Life Satisfaction Scale were used as data collection tools. Data analysis was carried out with two-stage structural equation modelling. According to the results, the final structural model accepted proposed indirect effects of adaptivity on adaptation results via adaptability and adapting responses. Also the final structural model observed direct effects of adaptivity on adapting responses and adaptability on adapting responses, adaptivity on adaptability and adaptability on adaptation results.
Keywords: Career adaptability; Career decision-making self-efficacy; Life satisfaction; Academic satisfaction; Self-esteem; Pre-service special education teachers; MAKING SELF-EFFICACY; SOCIAL SUPPORT; MEDIATING ROLE; WORK VOLITION; CONSTRUCTION; PERSONALITY; FIT; Psychology